Medical and Sports Equipment Online Business Practice in the Perspective of Positive Law and Islamic Law: Case Study at Desmira Medika Store, South Jakarta - Yahya A Ashiri; Irvan Iswandi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The purpose of this thesis was to find out the perspective of positive law and Islamic law on the online business practice of medical and sports equipment stores carried out by Desmira Medika Stores. The research method used by the researcher was a qualitative approach and the type of research was a case study (case upproach). The data collection techniques used in this study were observations, interviews, and case study documentation on the implementation of the business that occurred. Meanwhile, the data analysis technique was carried out through interviews, then verification, and drawing conclusions obtained.Based on the research that has been conducted by the writer, the following results are obtained: When associated with positive law, the online business is a legally valid transaction according to Article 1338 paragraph (1) of the Civil Code concerning the Principle of Freedom of Contract. According to Islamic law, online business is also a legitimate transaction because nothing contradicts or violates the pillars and conditions of the legality of buying and selling.